The acquisition of a miniature artificial language under various conditions of feedback - Lester Harold Gilbert (Department of Psychology, 2024)
The merits of special purpose computer languages for process control are discussed; it is proposed that the FORTRAN language is an adequate and generally available vehicle for the programming of on-line real-time experiments in Psychology, when used with the techniques which are described. l. A broad selective review of the literature on the acquisition of language by the young child yielded two questions which required investigation: the apparent incapacity in principle of current learning theory to account for such acquisition, and the apparent ineffectiveness of explicit reinforcement and feedback for accelerating language learning, An answer to the first question is sketched by a general theory of behaviour (du Preez, 1975), which is outlined, and a discussion of the necessity for maintaining correct levels of discourse in explaining a phenomena. 2. An experiment was carried out to provide evidence bearing upon the second question, the effects of informational feedback in language learning. The experiment illustrates the computer programming techniques discussed earlier, but primarily serves to demonstrate the kinds of studies which, line with the. general behavioural theory, may fruitfully explore language acq1..ns1.t1.on. Such studies, it is proposed, should employ miniature artificial languages and computer-controlled environments. University subjects were required to learn a miniature artHid.al language, and were given various combinations of semantic and syntactic informational feedback about their errors of production. The language dealt with the description of simple geomet_1~ical e!:ts nresented on a visual display· screen., ,~rh.ile the subjects interacted with the computer via a